Oxygen Reduction: Non‐Pt Nanostructured Catalysts for Oxygen Reduction Reaction: Synthesis, Catalytic Activity and its Key Factors (Adv. Energy Mater. 17/2016). Issue 17 (7th September 2016) - Xia, Zhonghong; An, Li; Chen, Peikai; Xia, Dingguo
Abstract : Fuel cell electric vehicles are at the center of extensive attention due to their high efficiency and pollution‐free traits. Electrochemical reaction occurs when fuels are subjected to oxidation at the anode catalyst layer while oxygen reduction reaction (ORR) takes place between oxygen, cations and electrons. Various ORR catalysts as potential alternatives to Pt are under intensive research right now. In article number 1600458, Dingguo Xia and co‐workers present recent progress on ORR electrocatalysts used in proton‐exchange‐membrane fuel cells (PEMFCs).